# -19j-5=-9-19j+4

## Simple and best practice solution for -19j-5=-9-19j+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -19j-5=-9-19j+4 equation:

Simplifying
-19j + -5 = -9 + -19j + 4

Reorder the terms:
-5 + -19j = -9 + -19j + 4

Reorder the terms:
-5 + -19j = -9 + 4 + -19j

Combine like terms: -9 + 4 = -5
-5 + -19j = -5 + -19j

Add '5' to each side of the equation.
-5 + 5 + -19j = -5 + 5 + -19j

Combine like terms: -5 + 5 = 0
0 + -19j = -5 + 5 + -19j
-19j = -5 + 5 + -19j

Combine like terms: -5 + 5 = 0
-19j = 0 + -19j
-19j = -19j

Add '19j' to each side of the equation.
-19j + 19j = -19j + 19j

Combine like terms: -19j + 19j = 0
0 = -19j + 19j

Combine like terms: -19j + 19j = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.`